Phantom sun - Bowen, Carl (Bowen, Carl. Shadow Squadron., 2014)
Lieutenant Commander Ryan Cross and his elite Shadow Squadron are deployed to Antarctica to recover a downed experimental aircraft, but Russian special forces and civilian scientists in Antarctica get in the way of it being an easy mission.